CHARACTER EDUCATIONAL VALUES IN ENCANTO ANIMATION MOVIE (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This research aimed to find out and describe the types of character educational values conveyed in Encanto animation movie. This research used descriptive qualitative method. The researchers used Kemendikbud formulation to analyze character educational values. The 18 types of character educational values, based on Kemendikbud includes religious, honesty, tolerance, discipline, hardworking, creativity, independent, democratic, curiosity, national spirit, love for the homeland, appreciate achievement, communicative, love peace, likes to read, cares about the environment, cares about social, and responsibility. In this research only 11-character educational values were found. They are honesty, tolerance, discipline, creativity, curiosity, love for the homeland, appreciate achievement, communicative, love peace, cares about social, responsibility. So, there are 7-character educational values that have not been conveyed in Encanto animation movie. They are religious, independent, democratic, hardworking, national spirit, likes to read, and cares about the environment. There are 58 dialogues conveyed as the character educational values. Those are 2 values of  honesty, 1 value of tolerance, 1 value of discipline, 3 values of creativity, 13 values of curiosity, 1 value of love for the homeland, 2 values of appreciate achievement, 4 values of communicative, 8 values of love peace, 22 values of cares about social, and 1 value of responsibility. Then, the researchers found the dominant character educational values in the movie is cares about social which is conveyed in 22 dialogues.
Keywords: Character Education; Merdeka Curriculum; Movie; Encanto.